Employees' attitudes towards family friendly policies - Kwong, Lai Cheng; Lee, Kum Chee (Penerbit Universiti Kebangsaan Malaysia, 2008)
As employees increasingly face challenges in balancing work with family commitments, the workplace could provide support and practical solutions to their stressful lives. Thus family friendly policies could play an important role in attracting and retaining workers. Family friendly policies are considered as any benefit or working condition that employees enjoy in order to achieve some balance in their family and working life. This study was conducted to determine the extent to which family friendly policies are practised in organizations in the Klang Valley, as well as the perceptions of employees towards such policies. A questionnaire was designed for the study. Based on the data collected from a sample of 113 workers, the findings revealed that a gap existed between what employees actually wanted and what organizations were offering in terms of these policies. Respondents favoured these policies, whether male or female, as well as with or without dependents. The findings have implications for employers, as a greater emphasis on these policies could affect the productivity and morale of workers.